2016
DOI: 10.1016/j.juro.2016.06.086
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and Biochemical Outcomes among African-American and Caucasian Men with Low Risk Prostate Cancer in the SEARCH Database: Implications for Active Surveillance Candidacy

Abstract: Purpose Racial disparities in the incidence and risk profile of prostate cancer at diagnosis among African-American men are well reported. However, it remains unclear whether African-American race is independently associated with adverse outcomes in men with clinical low risk disease. Materials and Methods We retrospectively analyzed the records of 895 men in the SEARCH (Shared Equal Access Regional Cancer Hospital) database in whom clinical low risk prostate cancer was treated with radical prostatectomy. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 32 publications
2
36
0
1
Order By: Relevance
“…In addition, MAA with low‐risk PCa have higher PCa‐specific mortality when treated compared to MEA . However, MAA continues to be enrolled in active surveillance protocols because there are other studies showing no significant upgrading or upstaging after RP . Nonetheless, analysis of active surveillance cohorts report that MAA is more likely to have progression and require active treatment .…”
Section: Causes For Prostate Cancer Disparitiesmentioning
confidence: 99%
“…In addition, MAA with low‐risk PCa have higher PCa‐specific mortality when treated compared to MEA . However, MAA continues to be enrolled in active surveillance protocols because there are other studies showing no significant upgrading or upstaging after RP . Nonetheless, analysis of active surveillance cohorts report that MAA is more likely to have progression and require active treatment .…”
Section: Causes For Prostate Cancer Disparitiesmentioning
confidence: 99%
“…Margin positivity and pathology Gleason stage were the major predictors of BCR‐free survival in our study, which only slightly differed by race likely due to smaller numbers of AA men (Table ), while race and predominant tumor location did not predict BCR‐free survival. The two previous studies that strictly included low‐risk patients with equal access to health care did not present results for margin status or Gleason stage; however, the SEARCH (Shared Equal Access Regional Cancer Hospital) study found no association (HR = 1.11, 95% CI = 0.81‐1.50, P = .52), while a study from New York Harbor VA hospitals found an association at 5 years (98% CA vs 82% AA, P = .006) for BCR‐free survival, but most likely lacked sufficient CA men for this finding to be replicated . Results from the SEARCH study with all‐risk patients also showed no association between CA and AA race and CaP metastasis (HR = 1.21, 95% CI = 0.87‐1.57, P = .26), CaP specific death (HR = 1.00, 95% CI = 0.61‐1.64, P = .99), and overall death (HR = 1.02, 95% CI = 0.90‐1.17, P = .76) .…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, Leapman et al. examined 895 men with LR‐prostate cancer and equal access to medical care, of whom 40% were AA, and found no significantly higher risks of pathological or stage upgrading, positive surgical margins, or BCR. Schulman et al.…”
Section: Discussionmentioning
confidence: 99%